Platelet Electrophoresis: The Present Position - Hampton, J. R; Mitchell, J. R. A (Thrombosis and Haemostasis, 1974)
Measurements of platelet aggregation and adhesion have proved disappointing in the study of individual subjects with, or at risk from, arterial disease. In this paper the technique of platelet electrophoresis is described, and it is shown that with this technique individual patients with coronary artery disease can be identified with a high degree of accuracy. Abnormal platelet electrophoretic behaviour is also described in the relatives of subjects who have had a myocardial infarction at an early age, and it is suggested that the platelet abnormality precedes clinically-detectable disease.The platelet abnormality is shown to be secondary to changes in the plasma, and experiments are described in which a start has been made in elucidating the nature of the plasma abnormality. Two plasma components are involved: one is probably adenosine diphosphate (ADP), and it is shown that ADP has two distinct effects on platelets; the other component is associated with the plasma low-density lipoproteins.The nature of the low-density lipoprotein abnormality that induces platelet changes that can be detected by this electrophoretic technique appear of extreme importance in the understanding of thrombosis. No specific chemical abnormality has been identified in these lipoproteins, but certain detergents are shown to have a similar effect on platelet electrophoretic behaviour. It is therefore suggested that there are changes in the surface-active, or detergent, properties of the lipoproteins in subjects with, or at risk from, arterial disease.